Selectivity in the synthesis of cyclic sulfonamides : application in the synthesis of natural products - Geoghegan, Kimberly (Springer Theses, Recognizing Outstanding Ph.D. Research, 2014)
In the area of organic chemistry one major challenge we are currently faced with is how to assemble potentially useful molecules in new ways that generate molecular complexity and in sequences that are as efficient as possible. Our efforts in this regard, specifically for the preparation of amino containing compounds incorporating an aromatic ring, are described in this doctoral thesis. We discovered an interesting regioselectivity in an intramolecular Heck reaction, which we studied for a series of substrates that are unbiased in terms of the size of the newly formed ring, where very high levels of selectivity in relation to the new carbon-carbon bond are typically observed. DFT calculations were performed to attempt to shed light on the reaction sequence. This regioselective Heck reaction, combined with the reductive removal of the temporary amino-protecting group, allowed us to synthesize the Sceletium alkaloids: mesembrane, mesembranol and mesembrine.